Progress of health care in rural India: a critical review of National Rural Health Mission - Gopalakrishnan, S.; Immanuel, A. (International Journal Of Community Medicine And Public Health, 2017)
National rural health mission (NRHM) was initiated in the year 2005 in eleventh five year plan, with the objective of providing quality health care services to the rural population. The mission brought out salient strategies by involving various sectors and forging partnerships with various organizations to unify health and family welfare services into a single window. Though the mission strived for a sustainable health care system, it did not envisage certain challenges in implementation. The public health system in India could take off from the foundations laid by the NRHM to overcome these challenges, in order to achieve various goals of health and development and put India on the road map of healthful development. The objective of this review article is to critically evaluate the implementation of national rural health mission and highlight its success and to make recommendations on the future health care planning and implementation in achieving universal health coverage for the rural India. NRHM has been a mammoth effort by the Union Government to build the public health infrastructure of the nation. The mission deserves its credit for empowering the rural India in health care, especially in States with poor health related indicators. NRHM has been a pioneer in reiterating the need for community participation, coupled with intersectoral convergence, to bring about a paradigm shift in the indicators, which has been reasonably achieved in most of the States. Taking forward the foundations laid by the NRHM, it is essential for the forthcoming policies and plans to focus on capacity building, not only on the infrastructure and technical aspects, but also on streamlining the health workforce, which is crucial to sustaining the public health infrastructure. The public health system in India should take off from the foundations laid by the NRHM. There is an imminent need to focus on forging a sustainable public private partnership, which will deliver quality services, and not compromise on the principles and identity of the public health system of the country, in its pursuit to achieve universal health coverage and sustainable development goals.